A triboelectric driven rectification free self-charging supercapacitor for smart IoT applications. (November 2022) - Shrestha, Kumar; Sharma, Sudeep; Pradhan, Gagan Bahadur; Bhatta, Trilochan; Rana, SM Sohel; Lee, Sanghyun; Seonu, Sookyeong; Shin, Youngdo; Park, Jae Y.
Abstract: The combination of energy harvester and energy storage in a single unit without an external complex circuit has sparked significant interest, owing to the potential for converting and storing energy in a single integrated device. Herein, a self-charging supercapacitor power cell (SPC) is proposed in which the energy generated from the triboelectric nanogenerator (TENG) is stored in a supercapacitor without power management or rectifier circuits via a 'tribo-electrochemical mechanism.' The SPC comprises poly (vinylidene fluoride-co-hexafluoropropylene) P(vdf-HFP) as a polymer separator, impregnated with ionic liquid electrolyte, and metal-organic framework derived cobalt nanoporous carbon/laser-induced graphene/copper (Co-NPC/LIG/Cu) electrode. Owing to the large surface area of SPC electrodes, an areal capacitance of 25.60 mF cm -2, the energy density of 0.0278 mW.h cm -2, and the power density of 0.089 mW/cm -2 are achieved. Furthermore, the self-charging SPC combines TENG and SPC into a single integrated device, with TENG generating 2.5 mW power, which can successfully charge the SPC to a maximum voltage of 210 mV within 9 s. Finally, the dynamic and static signals from the SPC device are utilized to control the 'jump' and 'duck' actions of T-REX in the gaming interface, and different SPC charge levels are utilized as a smart switch for turning on the smart home appliances. Thus, this study reveals the potential for charging the supercapacitor via TENG without any external circuit and provides significant insights into understanding the energy conversion process in self-charging supercapacitors. Graphical Abstract: ga1 Highlights: The energy generated from TENG is stored in a supercapacitor without any power management or rectifier circuits. The triboelectric layers in the self-charging SPC generate a power of 2.5 mW which can charge the SPC to 210 mV within 9 s. Owing to the high porosity and large surface area of the SPC electrodes, better electrochemical performance is achieved. This work aids in understanding the energy conversion process in self-charging SPC via triboelectrochemical mechanisms.